Special needs education and its implication in cultural diversity contexts: analysis from La Araucanía - Gutierrez-Saldivia, Ximena del carmen; Rivera Gutiérrez, Catalina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
This work aims at analyzing the special needs education through an epistemological reflection in contexts of social and cultural diversity. The analysis is developed, through the review of scientific literature in national and international regulations, using a documentary-descriptive method. The analysis considers the theory of abnormality that underlies the medical model applied to education, the theory of labeling and the perspective of power. The results reveal that Special Needs Education could make up a regulatory control to homogenize the school population, which is materialized through a classification and labeling system through examination and diagnostic procedures based on standards applied by the dominant group. It is concluded that, in order to move towards a possible conceptualization of Special Needs Education in indigenous territories such as La Araucanía, a new way of thinking is needed on issues related to special educational needs from a critical perspective in order to break western structure and canons.